Assessment of the normal pediatric pineal gland – MR findings of a single center retrospective study - Kumail khandwala; Kiran Hilal; Raima Zakaria; Nida Sajjad; Muhammad Azeemuddin; Zafar Sajjad (Journal of the Pakistan Medical Association, 2022)
Objective: To analyse the size and morphology of the normal pineal gland in the paediatric age group using magnetic resonance imaging. Method: The retrospective study was conducted at the Aga Khan University Hospital, Karachi, and comprised data of patients aged <18 years who had magnetic resonance imaging done between 2007 and 2017. Pineal size was estimated measuring its largest anteroposterior and supero-inferior diameters on sagittal T2-weighted sequences on any slice with maximal diameter. The width of pineal gland was measured on axial or coronal T2 sequences. The volume, morphology and enhancement patterns of the gland were also assessed. Data was analysed using SPSS 21. Results: Of the 200 patients, 116(58%) were males and 84(42%) were females. The overall mean age was 7.8±5.5 years. The mean anteroposterior dimension was 4.85±1.46mm, height 3.31±0.95mm, width 4.16±1.19, and volume 39.54±38.12 mm3. Mean size of cyst was 2.77±1.4mm (range: 1.2-7.5mm). No significant differences in the pattern of enhancement were found in different age groups (p>0.05). Conclusion: Comprehensive knowledge of the size of the typical pineal organ is useful for radiologists in the identification of pineal gland anomalies and the exclusion of neoplastic lesions. Key Words: Magnetic resonance imaging, Pineal gland, Pineoblastoma, Tumours, Cysts, Size.